2016
DOI: 10.1111/eth.12472
|View full text |Cite
|
Sign up to set email alerts
|

Structural Classification of Wild Boar (Sus scrofa) Vocalizations

Abstract: Determining whether a species' vocal communication system is graded or discrete requires definition of its vocal repertoire. In this context, research on domestic pig (Sus scrofa domesticus) vocalizations, for example, has led to significant advances in our understanding of communicative functions. Despite their close relation to domestic pigs, little is known about wild boar (Sus scrofa) vocalizations. The few existing studies, conducted in the 1970s, relied on visual inspections of spectrograms to quantify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 70 publications
(159 reference statements)
2
33
0
Order By: Relevance
“…red deer [ 52 ]. This is distinctive to the more “continual” vocal repertoires, e.g., in red fox ( Vulpes vulpes ) [ 36 ] and in the wild boar ( Sus scrofa ) [ 61 ], in which a noticeable number of intermediate vocalizations occurred along to distinctive call types. Transitional forms from one call type to another occurred only in 5.8% cases, similar to [ 19 ].…”
Section: Discussionmentioning
confidence: 93%
“…red deer [ 52 ]. This is distinctive to the more “continual” vocal repertoires, e.g., in red fox ( Vulpes vulpes ) [ 36 ] and in the wild boar ( Sus scrofa ) [ 61 ], in which a noticeable number of intermediate vocalizations occurred along to distinctive call types. Transitional forms from one call type to another occurred only in 5.8% cases, similar to [ 19 ].…”
Section: Discussionmentioning
confidence: 93%
“…Previous work has shown that two main call types, grunts and squeals, could be consistently identified while investigating the vocal repertoires of both domestic pigs ( Kiley, 1972 ; Tallet et al, 2013 ) and wild boars ( Garcia et al, 2016 ; Klingholz et al, 1979 ). Unlike squeals, the acoustic characteristics of grunts make them particularly well suited for highlighting formants because of their low F 0 ( Fitch and Hauser, 1995 ; Ryalls and Lieberman, 1982 ), even though the nasal production typical of this call type might slightly impair our ability to track formants compared with formants from calls of other mammalian species ( Charlton et al, 2011b ; Reby and McComb, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…those deemed to have a high enough signal-to-noise ratio and visible formants) were annotated with ‘Individual’ and ‘Series' using the ‘Annotate: To TextGrid’ function. Care was taken to identify true grunts clearly, as opposed to ‘grunt–squeals' which have quite different acoustic characteristics ( Garcia et al, 2016 ). Annotated grunts were extracted and average formant values were retrieved from each call via a custom-written Praat script (M.G.)…”
Section: Methodsmentioning
confidence: 99%
“…Research on the vocalizations of wild boar has shown that their calls can be categorized into grunts ( pulsatile, low-frequency sounds), squeals (noisy, harsh vocalizations in a broad frequency range), grunt -squeals (observations where both vocalizations were observed in a single vocalization), barks (isolated, short, high-intensity, non-harmonic vocalizations) and trumpets (harmonic calls with a high fundamental frequency) [136]. The recordings were analysed by extracting acoustic parameters and putting them through multinomial logistic regression models, and a hierarchical cluster analysis.…”
Section: Pigsmentioning
confidence: 99%